Studies on the in vitro hepatic microsomal formation of amides during the metabolism of certain secondary and tertiary benzylic amines - (:unkn) unknown (SPRINGER FRANCE, 2000)
Part of our interest during the last few years has been to investigate the possible intermediate(s) and mechanism(s) involved in the formation of amides from N-benzylic amines. A number of benzylic amines with different aryl and alkyl moieties introduced onto the constituent nitrogen were prepared, thus creating a wide variety of secondary, tertiary and heterocyclic benzylic amines with different logP and pKa characteristics (Tables I & II). In some experiments, the possible intermediates of this reaction, i.e. nitrones (Table III), imines (Table IV) and amides themselves (Table V), were used as substrates in our metabolic studies. Their in vitro hepatic microsomal metabolism was studied in order to obtain a structure/metabolic activity relationship for the formation of amides from benzylic amines. This communication reviews these studies and reports our conclusions as to the mechanism of formation of amides from N-benzylic amines.
Keywords: N-benzylic amines; metabolism; amide formation; liver microsomes; N-BENZYLANILINES; OXIDATION